Examining the Factors for Liberation from Fear and Sorrow from the Perspactive of the Holy Quran - Mehrbani , Rahmatullah; Amini, Addul Matin (Farah Research and Scientific Journal, 2025)
The value of liberation from fear and sorrow and attaining inner peace in life is undeniable. Modern humans utilize all available means to achieve this virtue and strive by any means to reach tranquility, having realized that happiness and success are not solely achieved through wealth and material gain. For centuries, humanity has wandered in search of this lost treasure, unaware of the true path to its attainment. This divine blessing becomes attainable when one frees themselves from material attachments and sets a higher goal beyond worldly pleasures. In short, one must trade the world for the hereafter and remove the love of worldly things—wealth, family, and desires—from the heart to connect with the true source of peace and comfort. Without obedience and submission to divine commandments, humans cannot find the right path. Therefore, what one seeks must be pursued through this route, as Islam is the only religion that provides a complete program for building both worldly and eternal life. The main objective of this research is to identify appropriate factors, in light of Quranic texts, to escape futile grief and anxiety and to create positive motivation for fulfilling the existential philosophy of human life. The applied method in this research is library-based, aiming to introduce the fundamental factors for liberation from fear and sorrow in life through the guidance of Quranic verses, highlighting the necessity and importance of the topic. The conclusion of this study is the liberation from the ominous shadow of fear and sorrow in life and attaining peace of mind, which is essential for successfully managing life and benefiting from this divine gift.